A realistic reading of the parable of the Lost Coin in Q : gaining or losing even more? - Van Eck, Ernest (Hervormde teologiese studies, 2019)
This article aims to present a realistic reading of the parable of the Lost Coin in Q. A realistic reading of the parable focuses on the social realia invoked by the parables, that is, the social realities and practices (cultural scripts) embedded by any given parable. As will be indicated, available documented papyri can be used to identify the possible social realia invoked by the parables, and this can help the modern reader to identify what is ‘normal’ or ‘abnormal’ in a parable being interpreted. This, in turn, can help the modern reader to come to grips with the probable intended meaning of the parable. In a realistic reading of the Lost Coin, it is argued that two things are important: the price and daily consumption of oil, and the Lost Coin being one of the gendered doublets in Q. Apart from proposing a possible meaning of the Lost Coin, it is also indicated that a realistic reading explains why the seeking of the woman is described as being ἐπιμελῶς [diligent].